The Man Without Qualities - Musil, Robert (New York Capricorn Books, 1965)
This magnificent novel, compared by critics with the best of modern masterpieces, demonstrates that one must turn to Proust, Mann and Joyce to find a talent of equal brilliance. Set in Vienna on the eve of World War I and peopled with some of the most memorable characters in modern literature, the book presents a profound, witty and striking portrait of life as it exposes the vanities, follies and eccentricities of the dying Austro-Hungarian Empire. Translated from the German and with a foreword by Eithne Wilkins and Ernst Kaiser.
Keywords: Literature